Integrated police center information system (spkt) at polsek lubuk raja - Muhammad Irvan Ma'ruf Irvan; Meilyana Winda Perdana (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
The National Police is an agency that provides public services in providing security to the community, one of which is in the Lubuk Raja sub-district, namely the Lubuk Raja Police which has a unit at the higher level, namely the Ogan Komering Ulu Police,One of the functions at the Lubuk Raja Police and the Resort Police and their staff is the Integrated Police Service Center (SPKT) which is tasked with providing services in the form of receiving reports. Receipt of reports and data processing at SPKT Lubuk Raja Police is still done manually, such as making reports using Microsoft Office Word in making reports so as to do file stacking and repetitive typing, and in giving register numbers and doing recording still using manual methods. By doing research at SPKT at Polsek Lubuk Raja the author thinks to create an Information System. In this study, the system development method used is the waterfall model with steps of system requirements analysis, system design, program code writing, testing, implementation and maintenance.